Effects of gellan-based edible coating on the quality of fresh-cut pineapple during cold storage - Azarakhsh, Nima; Osman, Azizah; Mohd Ghazali, Hasanah; Tan, Chin Ping; Mohd Adzahan, Noranizan (Springer, 2014)
The effects of gellan-based [gellan gum 0.56 % (w/v), glycerol 0.89 % (w/v) and sunflower oil 0.025 % (w/v)] edible coating on the respiration rate, physico-chemical properties and microbiological and sensory quality of fresh-cut pineapple during 16 days of storage (5 ± 1 °C, 85 ± 10 % RH) were evaluated. Uncoated fresh-cut pineapple was stored under the same condition and served as the control. For cross-linking reaction which was necessary for gel formation of gellan gum, a 2 % (w/v) calcium chloride solution that contained 1 % (w/v) ascorbic acid and 1 % (w/v) citric acid (as antibrowning agents) was used. The results obtained show that the respiration rate and weight loss of gellan-based coated samples were significantly (p < 0.05) lower than those of the uncoated samples during 16 days of storage at 5 °C. In addition, coated samples significantly (p < 0.05) maintained the firmness and colour of fresh-cut pineapple during low-temperature storage as compared to uncoated samples. The results obtained in this study also indicate that pH, titratable acidity and total soluble solids of coated and uncoated samples showed little changes during 16 days of storage at 5 °C. Gellan-based formulation did not show any antimicrobial effect, and no significant (p > 0.05) differences were found among total plate counts and yeast and mould counts for coated and uncoated samples. Total plate counts and yeast and mould counts for coated and uncoated samples reached 106 CFU/g (limit of shelf life acceptance for fruit-based products recommended by the Institute of Food Science and Technology in the UK) after 12 days of storage at 5 °C. In addition, the scores for all sensory characteristics at day 12 were significantly (p < 0.05) higher in coated samples as compared to control. Therefore, the results obtained in this study indicate that gellan-based edible coating formulation has the potential to maintain the quality of fresh-cut pineapple during low-temperature storage for about 12 days.